(untitled) (Research, Society and Development, 2020)
Water resource management is an essential tool for more conscious and sustainable consumption of water. However, urban growth and the expansion of industrial activities intensify the use of water resources, causing significant impacts on the demand x availability relationship. This accelerated and disordered growth directly impacts the available natural resources, since the occupation of new areas without planning affects the soil, local vegetation and water resources. In this context, the impacts on the available water resources are great, therefore, the management of water resources is fundamental to guarantee the qualitative and quantitative inspection and control of water. The granting of the use of water resources is one of the main management tools established under Law No. 9.433/97 that regulates the National Water Resources Policy. Thus, this study aimed to survey the uses granted by the State Secretariat for the Environment and Sustainability - SEMAS, to the municipality of Parauapebas-PA, in order to assess which are the main users and main purposes of water use in the region. An analysis was also carried out of changes in natural scenarios, which impact water resources. As a result of this study, it was found that the predominant uses for the municipality are to meet the mining activity, in which the highest flow rates granted are granted. The de-characterization of the soil in urban areas consists of aggravating and compromising the municipality’s water resources, causing the silting up of water bodies. The application of greater inspection in installed enterprises will contribute to the adequate planning of urban expansion, as well as the control and use of urban land.